OFFSET
0,2
COMMENTS
[Empirical] a(base,n)=a(base-1,n)+7^(n-1) for base>=3n-2; a(base,n)=a(base-1,n)+7^(n-1)-2 when base=3n-3.
FORMULA
G.f.: (1+9*x-84*x^2-2*x^3+321*x^4+70*x^5-178*x^6-26*x^7+13*x^8+2*x^9) / (1-12*x+33*x^2+36*x^3-125*x^4-55*x^5+70*x^6+16*x^7-5*x^8-x^9) (conjectured). - Colin Barker, Jul 18 2017
PROG
(S/R) stvar $[N]:(0..M-1) init $[]:=0 asgn $[]->{*} kill +[i in 0..N-2](($[i]`-$[i+1]`>3)+($[i+1]`-$[i]`>3))
CROSSREFS
KEYWORD
nonn,base
AUTHOR
R. H. Hardin, Dec 27 2006
STATUS
approved